Antibiotic Resistance in the Alternative Lifestyles of Campylobacter jejuni - Rossi, Daise Aparecida; Dumont, Carolyne Ferreira; Santos, Ana Carolina de Souza; Vaz, Maria Eduarda de Lourdes; Prado, Renata Resende; Monteiro, Guilherme Paz; Melo, Camilla Beatriz da Silva; Stamoulis, Vassiliki Jaconi; Santos, Jandra Pacheco dos; Melo, Roberta Torres de (Frontiers in Cellular and Infection Microbiology, 2021)
Campylobacter jejuni is the main pathogen identified in cases of foodborne gastroenteritis worldwide. Its importance in poultry production and public health is highlighted due to the growing antimicrobial resistance. Our study comparatively investigated the effect of five different classes of antimicrobials on the planktonic and biofilm forms of 35 strains of C. jejuni with high phylogenetic distinction in 30 of them. In the planktonic form, the existence of susceptible strains to colistin (7/35 – 20%) and resistance to meropenem (3/35 – 8.6%) represent a novelty in strains evaluated in Brazil. In biofilms formed with the addition of chicken juice, the number of resistant strains was significantly higher for colistin, erythromycin and meropenem (100%), but the susceptibility to tetracycline was shown as a control strategy for specific cases. High concentrations (1,060 ± 172.1mg/L) of antibiotics were necessary to control the biofilm structure in susceptible strains in the planktonic form, which is consistent with the high biomass produced in these strains. Stainless steel and polyurethane were the most (BFI=2.1) and least (BFI=1.6) favorable surfaces for the production of biomass treated with antimicrobials. It is concluded that the antimicrobial action was detected for all tested drugs in planktonic form. In sessile forms, the biomass production was intensified, except for tetracycline, which showed an antibiofilm effect.